THE EFFECT OF STUDENT TEAM ACHIEVEMENT DIVISION TECHNIQUE AND THE ACHIEVEMENT MOTIVATION ON THE WRITING ACHIEVEMENT OF THE TENTH YEAR STUDENTS OF SMA NEGERI 4 SINGARAJA IN THE ACADEMIC YEAR 2011/2012 - AK, Budiarta,; N, Padmadewi,; G, Budasi, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract Â  This thesis aimed at investigating whether the implementation of Student Team Achievement Division (STAD) technique and the studentsâ learning motivation gave a significant effect to the studentsâ writing achievement. The study was an experimental study by applying 2x2 factorial designs. The population was 6 classes (240 students) of grade X in SMA Negeri 4 Singaraja in the academic year 2011/2012, in which 2 classes were samples which were assigned into two groups, i.e. experimental group and control group, by Cluster Random Sampling. The research data were collected through tests that were analyzed by using Statistical Two-Way Anova and Tukey Test. The result shows that, first, there was a significant different on the studentsâ writing achievement between the students who were taught by using STAD Technique and Conventional Technique. Second, there was a significant interactional effect on the studentsâ writing achievement between the technique applied and the studentsâ learning motivation. Third, there was a significant difference on the studentsâ writing achievement between the students who had high learning motivation when they were taught by using STAD Technique and Conventional Technique. Fourth, there was no any significant difference between the studentsâ writing achievement of the students who had low learning motivation when they were taught by using STAD Technique and Conventional Technique. Five, there is a significant difference on studentsâ writing achievement between the students with high achievement motivation and the students with low achievement motivation taught by using STAD Technique. The last, there is a significant difference on studentsâ writing achievement between the students with high achievement motivation and the students with low achievement motivation taught by conventional technique. Â  Key words: Student Team Achievement Division (STAD) technique, achievement motivation, writing achievement.